Analysis of occupational hazards and accidents in land transportation in Peru - García Benites, Fidel (2023)
The purpose of this article was to identify occupational risks and accidents in the area of supervision and oversight of the Superintendence of Land Transportation of People, Cargo and Merchandise - Deconcentrated Unit of Lima - Callao. Currently, there is no research related to occupational risks and accidents during the workday in this agency. The present research was of the experimental type, descriptive level and causal transectional design. The instruments used were an observation guide, the format of internal occupational health and safety inspections and a questionnaire applied to 120 participants. The results showed that 70.8% of the participants did not receive constant training on topics related to risks at work; on the other hand, 92.5% have not suffered minor, serious or incapacitating accidents due to inadequate use of personal protective equipment; 53.3% mentioned that they have been exposed to physical risks, 87.5% to ergonomic risks. It was concluded that the workers did not receive training, were exposed to physical and ergonomic risks, but did not have accidents due to them. Better control of risks and identification of the causes that originate them are recommended in order to provide plans to minimize the current risks in the work environment in the area of supervision and control of land transportation.